Distribution of Dengue Vectors during Pre- and Post-Monsoon Seasons in Higher Attitudes of Nilgiri Hills of Western Ghats, India. (17th December 2013) - Ravikumar, R.; Reegan, A. Daniel; Chandrasekar, P.; Kumar, C. Senthil
Abstract : Entomological survey was carried out to record dengue vectors during pre- and post-monsoon seasons in 2012 from different breeding places in residential and forested areas of different altitudes of the Nilgiris, namely, Mettupalayam (330 mts), Kallar (400 mts), Burliar (900 mts), Marapalam (1050 mts), and Coonoor (1800 mts). Results showed that maximum number of dengue vector breeding was recorded at Mettupalayam during pre-monsoon season followed by Kallar, Burliar, Coonoor, and Marapalam. The post-monsoon season survey also revealed that the maximum number of dengue vector breeding was found at Mettupalayam, followed by Burliar, Coonoor, and Kallar, and Aedes immature was not found in Marapalam. Ae. aegypti species was recorded in all the study areas during pre- and post-monsoon seasons. Whereas Ae. albopictus was recorded only at Mettupalayam, Kallar, and Burliar during pre- and post-monsoon seasons. Besides these two dengue vectors, a nonvector species Ae. vittatus (n = 9 ) was also recorded at Kallar and Burliar.